Validity and Reliability of a Jordanian Version of the Adaptive Behavior Assessment System (ABAS-II) in Identifying Adaptive Behavior Deficits among Disabled Individuals in Jordan - Safa M. AlAli; Jameal M. Al Smady (Journal of Educational and Psychological Studies, 2015)
The purpose of this study was to investigate the validity and the reliability of the Jordanian version of the Adaptive Behavior Assessment System (ABAS-11, 2003) in detecting the manifestations of the deficit in adaptive behavior skills of performance on the teacher form, in Jordan. The sample of this study consisted of 200 normal students. Also, another 200 disabled children participated in the study. To achieve the aim of this study an Arabic version of teacher form was prepared (ABAS-II) in its second version. It was refereed by a group of specialists where their agreement reached 80%, thus resulting in 136 items distributed over 9 domains. Indication of concurrent validity in the Jordanian version was calculated as it was correlated with the one prepared by Al-Kilani and Al-batsh (1981) (r = 0.86). The reliability of the Jordanian version was investigated through test re-retest (0.92) and alpha coefficient (0.98).